Time-Frequency Nexus between Tourism Development, Economic Growth, Energy Consumption, and Ecological Footprint in Singapore - Ngoc, Bui Hoang; Hai, Le Mai (Journal of Reviews on Global Economics, 2022)
Singapore has been listed as one of the top-visited countries and has the highest ecological deficit. Despite the abundance of previous studies, the distinction between short, medium, and long term by decomposing tourism development, economic growth, energy consumption, and ecological footprint has been largely ignored. This study aims to investigate the lead-lag nexus structures between ecological footprint and Singapore’s economic activities from 1978 to 2016. By adopting the wavelet analysis and scale-by-scale Granger causality test, the outcomes show that energy consumption positively impacts ecological footprint at high frequencies, while tourism and economic growth positively drive ecological footprint at high and medium frequencies. We also find that the positive impact of macroeconomic variables on ecological footprint has not been evident since 2003. Additionally, the wavelet-based Granger test confirms a bi-directional causal between economic growth and ecological footprint at all frequencies, whilst there is a bi-directional relationship between tourism, energy consumption, and ecological footprint at high frequency. Based on these findings, the research may further strengthen the belief of Singapore’s policy-makers on the promotion of tourism and suggests some helpful lessons for emerging countries.